Assessment of The Not Too Young to Run Law on Youth Political Participation in Gombe State (Integral Research, 2025)
The purpose of study is to assess whether the "Not Too Young to Run Law’’ in Nigeria influences level of youth political participation in Gombe State. From this survey conducted with 400 respondents in Gombe Central, the study revealed that the legislation has opened an avenue for youth involvement in politics and reduced barriers to entry into politics by young candidates. However, despite this advancement, the study identified challenges such as socioeconomic, financial constraints, imbalance mentoring, party politics and cultural issues as effective hindrances to youth participation. The study concluded that while the law has created more opportunities for youth, the identified challenges must be addressed for sustaining and expanding youth engagement in political activities. It recommended the need for targeted interventions to support young aspirants, media houses and political parties to educate voters, among others, to ensure the continued success of youth in politics.
Keywords: Youth, Political Participation, Not Too Young To Run, voters, Democracy, Political Parties, Gombe State & Nigeria.